Why I Am Worried about My Post PhD-degree Life - A Commentary - Jung-Im Shin (University of North Florida, 2013)
Public health is an area where we will always need professionally-prepared people, but despite desperate needs in higher education, some soon-to-graduate PhD students are concerned that there might not be a place for them. Furthermore, some are concerned about balancing school, work, and family life. Perhaps now more than ever public health professional programs and schools need to devote resources toward career counseling and job placement.